Values of artificial intelligence in marketing - XI, Yingrui (Institutional Knowledge at Singapore Management University, 2020)
Artificial Intelligence (AI) is causing radical changes in marketing and emerging as a competent assistant supporting all areas of the marketing field. The influences and impacts AI has created in various marketing segments have aroused much interest among marketing professionals and academic scholars. Comprehensive and systematic studies on the values of AI in marketing, however, are still lacking and the existing literature fragmented. This research provides a comprehensive review of the existing literature in the relevant fields as well as a series of systematic interviews using the Value-Focused Thinking approach to understand the values of AI in marketing. This research results in a means-ends network demonstrating the values and the relationships between the articulated values of AI in marketing by the subjects.